Developmental Dynamics of General and School-Subject-Specific Components of Academic Self-Concept, Academic Interest, and Academic Anxiety - Gogol, Katarzyna; Brunner, Martin; Preckel, Franzis; Goetz, Thomas; Martin, Romain (Frontiers in Psychology, 2016)
The present study investigated the developmental dynamics of general and subject-specific (i.e., mathematics, French, and German) components of students’ academic self-concept, anxiety, and interest. To this end, the authors integrated three lines of research: (a) hierarchical and multidimensional approaches to the conceptualization of each construct, (b) longitudinal analyses of bottom-up and top-down developmental processes across hierarchical levels, and (c) ipsative developmental processes across subjects. The data stemmed from two longitudinal large-scale samples (N = 3,498 and N = 3,863) of students attending Grades 7 and 9 in Luxembourgish schools. Nested-factor models were applied to represent each construct at each grade level. The analyses demonstrated that several characteristics were shared across constructs. All constructs were multidimensional in nature with respect to the different subjects, showed a hierarchical organization with a general component at the apex of the hierarchy, and had a strong separation between the subject-specific components at both grade levels. Further, all constructs showed moderate differential stabilities at both the general (.42 < r < .55) and subject-specific levels (.45 < r < .73). Further, little evidence was found for top-down or bottom-up developmental processes. Rather, general and subject-specific components in Grade 9 proved to be primarily a function of the corresponding components in Grade 7. Finally, change in several subject-specific components could be explained by negative, ipsative effects across subjects.